Controle da antracnose pós-colheita do mamão com leveduras killer - Lima, Jaqueline Rabelo de (2013)
This study aimed to isolate yeast able to produce and excrete the toxin from killer tropical fruits, to act in the biological control of plant pathogens in postharvest. A total of 580 yeasts strains, isolated from Ceara State of Brasil, were evaluated for their ability to produce killer toxin. Of these strains, 29 tested positive for the killer phenotype and were further evaluated for their ability to control Colletotrichum gloeosporioides germination in vitro. All yeast strains that expressed the killer phenotype were characterized by sequencing the D1/D2 regions of the large subunit of the rRNA gene. Five yeast strains provided a significant reduction in mycelial growth and conidial germination of C. gloeosporioides in vitro, especially Meyerozyma guilliermondii, which was able to reduce the fungal mycelial growth on solid medium (PDA) by 60% and block 100% of conidia germination in liquid media (PDB). Filtering and autoclaving the liquid cultures had no effect on the growth of the pathogen. These results indicate the potential use of antagonist yeasts isolated from tropical fruits in the control of anthracnose caused by C. gloeosporioides in papaya. Further elucidation of main mechanisms involved on anthracnose control by these yeasts could be helpful for the development of biocontrol techniques related to the management of this disease in tropical fruits. The efficiency of two killer yeast strains, with better results in vitro were tested in vivo against C. gloeosporioides, Wickerhamomyces anomalus (strain 422) and Meyerozyma guilliermondii (strain 443), as biocontrol agents against C. gloeosporioides, a postharvest anthracnose agent of papaya and other tropical fruits, was assessed. These strains were previously selected through in vitro assays, but in the present study, their in vivo action was assessed. In addition, the influence of phytopathogen inoculation time on the fruit in combination with the use of the biocontrol agent was also assessed. Through the use of scanning electron microscopy (SEM), we assessed mycoparasitism as an antagonistic mechanism of action. In addition, two hydrolytic enzymes, chitinase and β-1, 3 glucanase, were assayed. Our results indicated that W. anomalus (strain 422) and M. guilliermondii (strain 443) reduced the disease occurrence by 24.62% and 20.68%, respectively, for up to 6 days after inoculation, when applied 3 hours before the phytopathogen and incubated in a wet chamber (95% relative humidity) at 28°C. The time of yeast inoculation had a significant effect on its antagonistic action. Application of the yeasts 12 or 24 hours before the phytopathogen inoculation resulted in 13.75% and 30% of disease reductions for W. anomalus (strain 422) and 31.35% and 41.17% reductions for M. guilliermondii (strain 443), respectively. Electron micrographs confirmed mycoparasitism by clearly indicating the interaction of the yeasts with C. gloeosporioides hyphae, causing, in some cases, a loss of turgor and yeast penetration of walls with marked concavity formation on hypha cell walls. The efficiency of two killer yeasts, Wickerhamomyces anomalus (strain 422) and Meyerozyma guilliermondii (strain 443), which showed better results in tests in vtro and in vivo, associated with five different application vehicles was assessed for the protection of papayas postharvest. In this study, after 90 days of incubation at 4°C, W. anomalus (strain 422) and M. guilliermondii (strain 443) were viable with all application vehicles tested. Fruits treated with different formulations (yeasts + application vehicles) had a decreased incidence of disease (by at least 30%) compared with untreated fruits. The treatment of W. anomalus (strain 422) + 2% starch lowered disease occurrence by 48.3%. The most efficient treatments using M. guilliermondii (strain 443) were those with 2% gelatin or 2% liquid carnauba wax, both of which reduced anthracnose by 50% in postharvest papayas. Electron micrographs of the surface tissues of the treated fruits showed that all application vehicles provided excellent adhesion of yeast to the surface. The formulations based on starch (2%), gelatin (2%) and carnauba wax (2%) were the most efficient at controlling fungal diseases in postharvest papayas